PENGARUH PENGUNGKAPAN STRUKTUR CORPORATE GOVERNANCE TERHADAP KECURANGAN PELAPORAN KEUANGAN - Haryani -; Muchamad Syarifuddin (LPPM STIE DHARMAPUTRA SEMARANG, 2022)
ABSTRACTThe purpose of this study is to examine the effect of corporate governance structure on the likelihood of fraudulent financial reporting. The dependent variable used in this study is fraudulent financial reporting. Meanwhile, independent variables used in this study are the disclosure of corporate governance structure such as the number of the board of commissioners member, board members with international experiece, audit committee effectiveness, internal audit effectiveness, and the existence of Big-4 audit firms. The population in this study consists of all manufacturing companies listed in Indonesia Stock Exchange during 2019-2020. The sampling method used is purposive sampling. The total number of samples in this study were 242 companies. Data analysis was performed by the descriptive statistic analysis and hypothesis test with logistic regression analysis. The result of this study shows that board members with the international experience, audit committee effectiveness, internal audit effectiveness, and the existence of Big-4 audit firms have significant positively effect in reducing the likelihood of fraudulent financial reporting. However, the number of the board of commissioners member have no significant effect on the likelihood of fraudulent financial reporting. Keywords:corporate governance, fraudulent financial reporting, board members, audit ABSTRAKTujuan dari penelitian ini adalah untuk menguji pengaruh struktur corporate governance terhadap kemungkinan terjadinya kecurangan pelaporan keuangan. Variabel terikat yang digunakan dalam penelitian ini adalah kecurangan pelaporan keuangan. Sedangkan variabel independen yang digunakan dalam penelitian ini adalah pengungkapan struktur corporate governance seperti jumlah dewan komisaris, anggota dewan dengan pengalaman internasional, efektivitas komite audit, efektivitas audit internal, dan keberadaan KAP Big-4. Populasi dalam penelitian ini adalah seluruh perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia selama tahun 2019-2020. Metode pengambilan sampel yang digunakan adalah purposive sampling. Jumlah sampel dalam penelitian ini sebanyak 242 perusahaan. Analisis data dilakukan dengan analisis statistik deskriptif dan uji hipotesis dengan analisis regresi logistik. Hasil penelitian ini menunjukkan bahwa anggota dewan dengan pengalaman internasional, efektivitas komite audit, efektivitas audit internal, dan keberadaan KAP Big-4 berpengaruh positif signifikan dalam mengurangi kemungkinan terjadinya kecurangan pelaporan keuangan. Namun jumlah anggota dewan komisaris tidak berpengaruh signifikan terhadap kemungkinan terjadinya kecurangan pelaporan keuangan. Kata kunci: corporate governance, kecurangan pelaporan keuangan, anggota dewan, audit